Mapping of wave packet dynamics at conical intersections by time- and frequency-resolved fluorescence spectroscopy : a computational study - Chen, Lipeng (2021)
Monitoring of wave packet dynamics at conical intersections by time- and frequency-resolved fluorescence spectroscopy has been investigated theoretically for a three-state two-mode model of a conical intersection coupled to a dissipative environment. The ideal and the actually measurable time- and frequency-gated fluorescence spectra are accurately and efficiently simulated by combining the hierarchy equations-of-motion method for dissipative quantum dynamics with the methodology of the equation-of-motion phase-matching approach for the calculation of spectroscopic signals. It is shown that time- and frequency-resolved fluorescence spectra reveal essential aspects of the wave packet dynamics at conical intersections and the effects of environment-induced dissipation. The results of the present work indicate that fluorescence up-conversion spectroscopy with femtosecond time resolution is an efficient tool for the characterization of ultrafast dynamics at conical intersections.